Environmental Credit Risk Management in Banks and Financial Service Institutions - Weber, Olaf (Business Strategy and the EnvironmentBusiness Strategy and the Environment, 2012)
How do Canadian banks integrate environmental risks into corporate lending and where are they located compared with their global peers? In this paper we report a mixed method analysis of the integration of environmental risks into the credit management. The qualitative and quantitative analyses suggest that all analyzed Canadian commercial banks, credit unions and Export Development Canada manage environmental risks in credit management to avoid financial risks. Some of the institutions even connect environmental and sustainability issues with their general business strategies. Compared with other countries, Canadian banks are best in class, as all six Canadian commercial banks, comprising over 90 percent of Canadian assets, systematically examine environmental risks for credits, loans and mortgages. We conclude that Canadian banks are proactive regarding environmental examinations of loans and that there is a need for a more accountancy related reporting on environmental risk management in financial institutions. Further research is needed to be able to calculate costs and benefits of integrating environmental and sustainability issues into the credit risk management. Copyright © 2011 John Wiley & Sons, Ltd and ERP Environment.
Keywords: Canada; commercial banks; corporate social responsibility; environmental credit risk; risk management; sustainability